Sílica gel obtida de escória de alto forno: Marabá, Pará - REBELO, Monaliza Maia (Universidade Federal do Pará, 2017)
Silica gel with similar properties to commercial silica was obtained from blast furnace slag (EAF) using digestion with hydrochloric acid. The EAF-silica was obtained and characterized by different techniques. The results showed that the EAF-silica obtained was amorphous, with 99.7% purity and specific area 282 m2/g. It presented high hydrophilic character (12.27%), with constitution water of ~ 6.18%, which was confirmed by mass loss in thermogravimetric analysis. The EAF-silica particles had micrometric sizes (< 1 µm) with aggregates, unimodal size distribution and D50 7.0 µm.